Religiosity and Sexual Behavior Tense Relationships and Underlying Affects and Cognitions in Samples of Christian and Muslim Traditions - Rigo, Caroline; Saroglou, Vassilis (2018)
Religion's historical mistrust of sexuality shapes people's behavior by inhibiting liberal sexuality. Still, it is unclear whether this inhibitive role also includes common, normative sexual behavior, particularly in secularized contexts. Moreover, the possible mediating effects emotions, affects, and thoughts have on the association between religiosity and restricted sexuality have never been integrated into a single model. Finally, cross-religious differences in common sexual behavior have still yet to be documented. We addressed these three issues in two studies, with samples of Catholic and Muslim tradition (total N = 446). Consistently across samples, religiosity predicted, either directly or indirectly, less frequent common heterosexual behaviors and masturbation, partly through sexual guilt and inhibition, and/or decreased sexual fantasy and the search for sexual pleasure. However, married Muslims' religiosity, unlike Catholics', did not directly undermine fertility-oriented sexuality and the search for pleasure. Religion's role in restricting sexuality seems to be rooted in deep psychological rationale.
Keywords: Catholicism; Islam; Disgust; Guilt; Religion; Sexual Behavior